PHYSICAL EDUCATION - GUARANTEE OF HEALTH AND BEAUTY - Sultanov U. I. (Galaxy International Interdisciplinary Research Journal, 2023)
10% of human health is from medicine, the remaining 90% is from him It is not a secret to anyone that it consists of physical fitness and a healthy lifestyle. Regular physical training and sports are a passport to age-free appearance and disease-free aging.